When People Don’t Realize Their Career Desires: Toward a Theory of Career Inaction - Verbruggen, Marijke; De Vos, Ans (Academy of Management Review, 2020)
Career decisions are at the core of the career literature. Most current career theories focus on how career decisions are enacted and, in the end, realized. However, empirical evidence shows that people often do not realize their career desires. For instance, many people who have turnover intentions stay in their organization, and people with entrepreneurial desires often turn out to be wantrepreneurs (i.e., people who talk about starting a business without doing anything to realize it). Although structural barriers sometimes inhibit people from realizing a desired change, there are also indications that people often do not even mobilize into action, or give up prematurely, when trying to realize their career desires. This explanation, however, has rarely been acknowledged, let alone studied. To address this gap, we develop a theory of career inaction. We define career inaction as the failure to act sufficiently over some period of time on a desired change in one’s career. Building on the psychology of doing nothing, we explain why and when career inaction may occur and how it can impact people, even in the longer run. Our propositions may guide career researchers to think about and include career inaction in their future studies.